Depression and Insomnia of Front-Line Medical Staff During the COVID-19 Outbreak in China: An On-Line Cross-Sectional Study - Zhang, Donglin; Luo, Hailong; Xiao, Litian; Zhang, Zhun; Huang, Jianqing; Li, Xiaoqin; Zhu, Hongke; Lai, Cuiwei (Frontiers in Psychology, 2022)
Purpose: During the COVID-19 outbreak, medical staff working in high-risk workplaces have a higher rate of epidemic infection, face heavy workload and pressure as well, which make them suffer psychological problems much easier than others. In order to understand the mental health of medical staff in epidemic, explore the characteristics of medical staff susceptible to negative psychological emotions during the outbreak of public safety and health events, at the same time, provide corresponding prevention and intervention measures to help them relieve negative emotions, this study compared psychological symptoms of front-line and non-front-line medical staff, then explored its influencing factors. Methods: This research investigated 5,924 medical staff in Guangdong, Beijing, Hubei, Hainan, Jiangxi and Henan in China. The questionnaires were released online by Questionnaire Star, and level of depression, anxiety, insomnia and social support were measured by Patients’ Health Questionnaire Depression Scale-9 item (PHQ-9), Generalized Anxiety Disorder 7-item Scale (GAD-7), Insomnia Severity Index (ISI) and Social Support Rating Scale (SSRS). Results: The depressive, anxious and insomnic scores of front-line medical staff in COVID-19 epidemic period were higher than those of non-front-line with significant differences (P<0.001). In addition, front-line nurses went through most serious psychological problems. Age, education and anxious level were the influencing factors of depression and insomnia in front-line medical staff. Among them, age was a protective factor for depression (OR=0.71<1, P=0.001<0.05, Beta=-0.34), while educational level was a risk factor for insomnia (OR=1.27, P=0.02<0.05, Beta=0.24). Conclusions: During the epidemic, front-line medical staff would experience more serious psychological problems, especially those who were younger, less experienced, and insufficiently educated. Attention should be paid to giving them psychological assistance and psychological intervention in the future.